Trend Analysis of Tides Level and Projection Sea Level Rise On the West Coast of Peninsular Malaysia - Md Ali, Zarina; Tan, Lai Wai; Ahmad, Noor Aliza; Musa, Sabariah (International Journal of Integrated Engineering, 2023)
Globally, sea levels are rising due to climate change caused by humans. Current and future sea level rise will have a variety of effects, particularly on coastal infrastructure. This study analysed the tidal level trend and projected sea level rise along the western coast of peninsular Malaysia using tide level records collected between 1986 and 2012. The seasonal Mann-Kendall test and linear trend were used to determine the tide level trend over time and to predict sea level rise for 2050 and 2100. Based on a confidence interval of 95%, the results of the analysis indicated a rising trend at all stations. Tau values for the Mann-Kendall test range between 0.16 and 0.33, while seasonal Mann-Kendall values range between 0.18 and 0.41. Based on the sea level projection analysis, the mean sea level will rise between 8.77 cm and 14.29 cm in 2050, and between 20.44 cm and 33.20 cm in 2100. In conclusion, the sea level trend at all stations on the west coasts of peninsular Malaysia exhibits an upward trend.